Sport coaches` education, training and professional development: the perceptions and preferences of coaches of elite athletes with disability in Australia - Wareham, Y.; Burkett, B.; Innes, P.; Lovell, G. P. (Sport in Society: Cultures, Commerce, Media, Politics, 2018)
Coaching is a critical factor in the development, training and success of athletes, yet coaching of athletes with disability is significantly underrepresented in the research literature. This research explored the education, training and professional development experiences of coaches of elite athletes with disability. Semi-structured interviews were held with 12 coaches of elite athletes from sports including swimming, athletics, cycling, canoeing, triathlon, equestrian sport and wheelchair basketball. Results showed that coaches reported there was very little inclusion of information specific to disability in the accredited training courses for the sports included in this study. Furthermore, collegial collaboration, experiential learning and iterative self-reflection were the three professional development sources considered to be of most value.